Lactylated NAT10 contributes to elesclomol-triggered cuproptosis via the NAT10/ac4C-DLAT-mRNA/DLAT positive feedback loop in CRC - Wen-Dong Yang; Meng-Ru Lu; Qi Shen; Pei-Heng Zhou; Yang Diao; Shan Xia; Ya-Chun Lu; Yong-Qiang Cui; Bing-Qiang Li; Wen-Xia Xu; Lin Chen; Chao Zhang; et al. (Proceedings of the National Academy of Sciences, 2026)
Cuproptosis represents a promising therapeutic strategy for cancer; however, its clinical application remains limited. We observed elevated copper levels and increased expression of DLAT, a key procuproptosis gene, in colorectal cancer (CRC) tissues, suggesting inherent susceptibility to cuproptosis. Furthermore, NAT10 enhances DLAT mRNA stability by mediating its N 4 -acetylcytidine (ac4C) modification, thereby promoting cuproptosis. We also discovered that lactylation of NAT10 at lysine 426 (K426) enhances NAT10 catalytic activity. Conversely, SIRT1 mediates the delactylation of NAT10-K426, leading to the inhibition of cuproptosis. The combination of elesclomol (a cuproptosis inducer) and selisistat (a SIRT1 inhibitor) effectively induced cuproptosis in CRC. Notably, the reduction of soluble DLAT induced by elesclomol treatment was found to enhance NAT10-K426 lactylation. Moreover, DLAT supplementation establishes a positive feedback loop that amplifies cuproptosis. These results underscore the critical role of nonhistone NAT10 lactylation in tumor cuproptosis and highlight the therapeutic potential of targeting this pathway for CRC treatment.